Intelligent fuzzy controller of twin-rotor MIMO system - Che Soh, Azura; Yeo, Lay Ting (2012)
An assessment on flight control system of an aircraft system was done based on time response performance on intelligent controller of fuzzy logic control (FLC). The assessment was compared with modern controller of linear quadratic controller (LQR). Firstly a mathematical model of a two Degree of Freedom (2-DOF) helicopter was derived to describe the dynamic of the aircraft. Then FLC was developed to control the pitch angle of 2-DOF helicopter so that disturbance has minimal effect on pitch and yaw control. The fuzzy logic controller designed is similar to a proportional controller where only error and change of error are used as inputs into the controller. Simulation was conducted using Matlab Simulink software where Simulink model of 2DOF helicopter which developed by Quanser was used and modification was mainly done on the controller subsystem part where a FLC was added. The simulation results for the pitch and yaw response controllers were presented in time domain. The performances of both pitch and yaw control systems were analyzed through step’s response, thus to achieve better performance.